Boardroom integrity and the crusade against fraud: Navigating corporate governance in Indonesia - Juhandi, Nendi (Journal of Economics and Business Letters, 2022)
This study delves into the intricate landscape of corporate governance within Indonesian corporations, scrutinizing its efficacy in deterring financial statement fraud. By amalgamating insights from a systematic literature review, quantitative analyses of secondary data, and logistic regression methods, the research elucidates the multifaceted interplay between various governance mechanisms and the persistence of fraudulent activities. Central to our findings is the pivotal role of board size in enhancing corporate oversight and mitigating fraud, juxtaposed against the ambiguous impacts of other governance elements such as audit committee effectiveness and board experience. This complexity underscores the paramount importance of ethical leadership and the "tone at the top" in fostering a corporate culture steeped in integrity, which is instrumental in fraud prevention. The paper posits that the dual focus on strengthening structural governance frameworks and nurturing ethical corporate leadership is essential for safeguarding Indonesia's economic integrity and promoting sustainable development. Through this lens, the study not only contributes to the academic discourse on corporate governance but also offers actionable insights for policymakers, corporate leaders, and regulatory bodies striving to combat corporate fraud in Indonesia.